Understanding and preventing nonadherence and treatment dropout in adolescents and young adults with anxiety and depressive disorders - Waumans, Ruth C.; Muntingh, Anna D. T.; Batelaan, Neeltje M.; van Balkom, Anton J. L. M. (Frontiers in Psychiatry, 2023)
Dropout from psychological or pharmacological treatment for anxiety and depressive disorders is common. It is especially problematic in adolescents and young adults because of the adverse consequences for their development. Reasons for treatment dropout can be divided into therapy-process related factors, attitudinal aspects, and practical issues.Adjusting treatment to patient preferences and shared decision making, improving the therapeutic alliance, and interventions such as (family) psychoeducation, motivational interviewing, and help with practical issues are promising strategies to optimize engagement and adherence.